PERENCANAAN KAWASAN PESISIR PULAU DATOK DI KABUPATEN KAYONG UTARA SUKADANA KALIMANTAN BARAT - Sudrajat, Kiki; Budiyono, Debora; Nailufar, Balqis (Universitas Tribhuwana Tunggadewi, 2017)
Datok Island Beach located near at the National Park Palung Mount (TNGP) area. Datok Island beach has unspoiled landscapes, unique landscape beauty, wildlife biodiversity and high water biota. Datok Island has constraints on the lack of landscape management, the unavailability of public facilities for tourist visitors, and the threat of losing the king's ornamentation as a historical site. This study aims to plan the landscape of Datok Island Coastal Area. Data collection techniques using quantitative descriptive methods. This research activity was carried out based on ecosystem sensitivity analysis, object and aktraksi analysis, landscape visual analysis, social analysis, and regional carrying capacity. Most of the tourist attraction in the Datok Coastal area has the potential to be developed as a sustainable coast area. The Datok Coastal Tourism Development Zone in the classification of high potential is in the coast area with an area of 0.9 ha (9.84%). and forest area of 8.87 ha (90.16%). with moderate classification. Data collected for this study include primary data and secondary data. The results of the study show that the coast of Datok Island has an area of 9.84 ha consisting of core zones with area, special zone, buffer zone, and user zone. Planning Datok Coastal Zone as a sustainable tourism area. The concept of landscape consists of the concepts of space, vegetation, circulation, facilities and activities. Pantai Pulau Datok terletak di dekat kawasan Taman Nasional Gunung Palung (TNGP). Pantai Pulau Datok mempunyai lanskap yang masih alami, keindahan langskap yang khas, biodiversity satwa dan biota air yang tinggi. Pesisir Pulau Datok memiliki kendala belum adanya penataan lanskap, belum tersedianya fasilitas umum bagi para pengunjung wisata, dan terancam hilangnya ornamen makan raja sebagai situs bersejarah. Penelitian ini bertujuan untuk membuat perencanaan lanskap kawasan Wisata Pesisir Pulau Datok. Teknik pengumpulan data menggunakan metode deskriptif kuantitatif. Kegiatan penelitian ini dilakukan berdasarkan analisis kepekaan ekosistem, analisis objek dan aktraksi, analisis visusal lanskap, analisis sosial, dan daya dukung kawasan. Daya tarik wisata masyarakat di kawasan Pesisir Pulau Datok sebagian besar berpotensi untuk dikembangkan sebagai kawasan pesisir yang berkelanjutan. Zona pengembangan Wisata Pesisir Pulau Datok dalam klasifikasi potensi tinggi berada pada area pantai dengan luas seluas 0,9 ha (9.84 %). dan luas hutan 8.87 ha (90.16%). dengan klasifikasi sedang. Data yang dikumpulkan untuk penelitian ini meliputi data primer dan data sekunder. Hasil penelitian menunjukan Kaswasan Pesisr Pulau Datok yang memiliki luas 9.84 ha yang terdiri dari zona inti dengan luas, zona khusus, zona penyangga, dan zona pemanfaat. Perencanaan Kawasan Pesisir Pulau Datok sebagai kawasan wisata yang berkelanjutan. Konsep lanskap terdiri dari konsep ruang, vegetasi, sirkulasi, fasilitas dan aktivitas.